The Impact of Bond Rating Announcement on Companies Listed Stock Returns: Evidence from Indonesia - Novyandri Taufik Bahtera (TIJAB (The International Journal of Applied Business), 2017)
This study aims to determine whether there is a difference between stock returns before and after the announcement of both increases and decreases in bond ratings. This study is classified as a case study with an observation period of 5 days before and 5 days after the announcement of the bond rating. The population of this study is all companies listed on the Indonesia Stock Exchange that announced the ratings of bonds from 1999 to 2009, which made a total of 331 bond ratings in 52 companies. The sample was chosen using a purposive sampling method and 24 samples were obtained for the announcement of the increase in bond ratings and 18 samples for the announcement of the bond rating decline. Data testing is done using paired sample t-test. Based on the results of the study it can be concluded that (1) there is no significant difference in stock returns around the date of the announcement of the increase in bond ratings. This indicates that the announcement of an increase in bond ratings does not bring information to investors. (2) There is a significant difference in stock returns around the date of the announcement of the decline in bond ratings. This indicates that the announcement of the downgrade of bonds carries information content for investors.